The difference of in-shoe plantar pressure between level walking and stair walking in healthy males. (9th June 2021) - Cho, Yun Jae; Lee, Choongho; Lee, Jae Hee; Kyung, Min Gyu; Lee, Kyung Hwan; Lee, Dong Yeon
Abstract: Stair walking is more demanding locomotion than level walking and can aggravate discomfort of the foot. The purpose of this study is to analyze plantar pressure distribution and pressure patterns during gait cycle at stair walking compared to level walking. Thirty-five healthy males with 23.4 ± 2 years old were included in this study after examining normality. They performed level walking, stair ascending, and descending in same type of shoes. Measurements of in-shoe plantar pressure including peak pressure, pressure-time integral were done by Pedar-X system, masked 7 regions. Also, pressures in each region throughout the gait cycle were analyzed from each type of walking. Statistical analysis was performed using repeated measure one way analysis of variance. Peak pressure in all regions except for the midfoot was higher during level walking than stair walking. Pressure-time integral in the forefoot, midfoot during stair ascending, and the forefoot during stair descending was higher than level walking. In gait cycle, first peak was produced in the heel and the second peak was produced in the hallux during level walking, whereas during stair ascent, the heel and midfoot were in first peak, and the second peak was in the hallux. During stair descent, the first peak were in the forefoot and the midfoot, and the second peak was in the forefoot. In healthy young male adults, forefoot and midfoot are significant regions in the way that they have higher pressure burdens than other foot regions during stair walking.